DHIKR AND THINKING INTEGRATION AS NON-DICOTOMIC CHARACTER EDUCATION DEVELOPMENT - Ma`arif, Muhammad Anas (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The importance of character education to make learners practice the virtues. Not only in the realm of intellectual but also the spiritual sphere should also be developed character. Because basically humans are not composed of the body only but consist of the spirit as well. For that, we need an integral education between the needs of the body and the soul. This study aims to describe and analyze the integration of dhikr and thought as the development of non-dichotomic and integral character education. This research uses literature research from the data of books that have been collected relevant to the theme. Zikr istiqomah and think systematically will bring out the character of the learner is integral. Dhikr ( tazkiyatun nafs ) and thought (knowledge) form the whole human character ( ulul albab ) as the development of integralistic character education. Character is not only in form through cognitive learning but also necessary habituation of religious activities